1993
DOI: 10.1089/aid.1993.9.331
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 2 Multiply Spliced Transcripts

Abstract: Viral transcripts, particularly those of the regulatory genes (e.g., rev) in lymphocytic cells chronically infected with human immunodeficiency virus type 2, consist of two types, differing in the structure of the leader sequence derived from the 5' long terminal repeat (LTR). Some transcripts undergo a specific splicing event within the 5' LTR, removing an intron consisting of a part of the R region whereas others do not. Because this spliced-out R region is a part of the trans-activation response element (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although both motifs are expected to be in close proximity to the cap structure, the much stronger stability of HIV-2 TAR could be responsible for reduced translational efficiency. However, the HIV-2 5′-UTR contains a 140 nt intron that is removed in multiple spliced transcripts (66). Interestingly, Lodmell and colleagues (67) recently showed that this intron could also be removed from the gRNA 5′-UTR resulting in an mRNA with enhanced translation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both motifs are expected to be in close proximity to the cap structure, the much stronger stability of HIV-2 TAR could be responsible for reduced translational efficiency. However, the HIV-2 5′-UTR contains a 140 nt intron that is removed in multiple spliced transcripts (66). Interestingly, Lodmell and colleagues (67) recently showed that this intron could also be removed from the gRNA 5′-UTR resulting in an mRNA with enhanced translation.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it is unknown whether cellular factors participate in the regulation of HIV-2 translation through TAR. However, destabilization of the TAR structure by removal of an intron present within the 5′-UTR (66,67) and the use IRES elements within the Gag coding region (32–35) confers two alternative ways to overcome TAR constraints and allow Gag and Gag-Pol production. Thus, the direct binding of eIF3 and the 40S ribosomal subunit to the Gag IRES (35) may allow the full-length unspliced HIV-2 gRNA to be associated with polysomes.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between HIV-1 and HIV-2 may also exist following transcriptional initiation. For instance, the HIV-2 LTR is significantly larger than the HIV-1 LTR, has been shown to undergo 5Ј LTR splicing, and has a complex secondary structure that may affect transcriptional trans-activation (4,7). While the exact effect this has on mRNA accumulation in vivo remains unknown, it is possible that differences in the LTR structure result in less-efficient transcriptional elongation and/or the switch from early to late transcripts in HIV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The limited homology is particularly evident in the 5Ј untranslated leader sequence: SIV has a significantly longer leader sequence than HIV-1 (33) and it possesses a functional intron within the long terminal repeat (6,10,40,43). For HIV-1, the encapsidation signal has been shown to be composed of at least four stem-loop structures distributed both at the 5Ј and 3Ј ends of the major SD site (1-3, 8, 14, 22, 24, 42).…”
mentioning
confidence: 99%